2017
DOI: 10.1007/s00125-017-4439-4
|View full text |Cite
|
Sign up to set email alerts
|

Lower corneal nerve fibre length identifies diabetic neuropathy in older adults with diabetes: results from the Canadian Study of Longevity in Type 1 Diabetes

Abstract: Abbreviations CNBD Corneal nerve branch density CNFD Corneal nerve fibre density CNFL Corneal nerve fibre length IVCCM In vivo corneal confocal microscopy ROC Receiver operating characteristic ROC-AUC Area under the ROC curveTo the Editor: There exists an urgent need to better characterise and identify the presence of early-stage diabetic neuropathy when therapy is most likely to be effective. The lack of an objective endpoint for early neuropathy has seriously hindered the evaluation of disease-modifying ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…This technique has advantages over skin biopsy as it is rapid and non-invasive, but it is not yet widely available. There is only a modest correlation with disease stage in any patient and the correlation is of limited utility in clinical practice 183184185. A recent study of nearly 1000 patients with type 1 and type 2 diabetes demonstrated the diagnostic validity of corneal confocal microscopy using a 12.5 mm/mm 2 optimal threshold for automated corneal nerve fiber length in type 1 diabetes (73% sensitivity, 69% specificity) and a 12.3 mm/mm 2 optimal threshold in type 2 diabetes (69% sensitivity, 63% specificity) 176.…”
Section: Diagnostic Approachmentioning
confidence: 99%
“…This technique has advantages over skin biopsy as it is rapid and non-invasive, but it is not yet widely available. There is only a modest correlation with disease stage in any patient and the correlation is of limited utility in clinical practice 183184185. A recent study of nearly 1000 patients with type 1 and type 2 diabetes demonstrated the diagnostic validity of corneal confocal microscopy using a 12.5 mm/mm 2 optimal threshold for automated corneal nerve fiber length in type 1 diabetes (73% sensitivity, 69% specificity) and a 12.3 mm/mm 2 optimal threshold in type 2 diabetes (69% sensitivity, 63% specificity) 176.…”
Section: Diagnostic Approachmentioning
confidence: 99%
“…Finally, the two patients with a history of MPNST had normal small-and large-fiber tests. 10,25 Our rate of abnormal NCS, indicating large-fiber neuropathy, was low. In addition, clinical findings of a length-dependent large-fiber neuropathy, such as symmetrical distal weakness, sensory loss, and abnormal distal reflexes, were also rare.…”
Section: Small-fiber Studiesmentioning
confidence: 72%
“…Thus, more studies are needed to determine whether this test is abnormal in a larger cohort of NF1 patients, as well as to determine how CNFL changes with time. For example, in diabetes, CNFL changes can predict the onset of clinically significant neuropathy …”
Section: Discussionmentioning
confidence: 99%
“…This was a cross-sectional study of 75 people enrolled in the second phase of the Canadian Study of Longevity in T1D. Participants with T1D were recruited among the 300 participants who took part in the mail-based survey based on geographical proximity to Toronto General Hospital and willingness to participate [23][24][25].…”
Section: Study Population and Data Collectionmentioning
confidence: 99%